COMPARISON OF THE SUCCESS OF EXTRACORPOREAL SHOCK WAVE LITHOTRIPSY (ESWL) WITH AND WITHOUT DJ STENTING IN PROXIMAL URETERIC STONE - Mudassar Saeed Pansota; Sharmeen Shafqat; Shafqat Ali Tabassum (Journal of University Medical & Dental College, 2020)
BACKGROUND & OBJECTIVE: There is disagreement in the use of ureteral double-J stent before the extracorporeal shock wave lithotripsy (ESWL), although most of the urologists suggest using stent in shock wave lithotripsy technique for stones bigger than 20mm, for preventing the risk of developing steinstrasse. To compare the success of ESWL with and without DJ stenting in proximal ureteric stone. METHODOLOGY: A total of 60 patients form both genders, between 15 to 55 years of age, with a single proximal ureteric stone, were included. Patients with solitary functioning kidney, multiple stones, pregnancy, pyonephrosis and sepsis were excluded. In Group-A, ESWL without DJ stenting was completed while in Group-B, ESWL with DJ stent placement was done. In all patients, at least 4 sessions were done fortnightly. Patients were followed regularly and ﬁnal success was noted after one month of completion of ESWL sessions. RESULTS: The mean age was 36.85 ± 8.61 years. From 60 patients, 29 (48.33%) were men and 231 (51.67%) were women.Mean body mass index (BMI) was 28.30±2.20 kg/m . The average size of the stone was 12.47 ± 2.57 mm. Success (according to stone removal) of Group-A (ESWL without DJS) was seen in 26 (86.67%) patients while in Group-B (ESWL with DJS) was seen in 16 (53.33%) patients with P-value of 0.005. CONCLUSION: This study concluded that success (in terms of stone clearance) of extracorporeal shock wave lithotripsy (ESWL) without DJ stenting is higher compared to with DJ stenting in upper ureteric stone.